Cytotoxicity of Ear Drop Excipients in Human and Mouse Tympanic Membrane Fibroblasts - Dirain, Carolyn O; Karnani, David N; Antonelli, Patrick J (Otolaryngology-head and neck surgery, 2020)
Commercial ear drops contain ingredients reported to be inactive. We sought to evaluate such excipients for possible cytotoxicity on human and mouse tympanic membrane (TM) fibroblasts. Prospective, in vitro. Tertiary academic center. Mouse and human TM fibroblasts were treated with 1:10 dilutions of benzalkonium chloride (BKC) 0.0025%, 0.006%, or 0.01%; benzyl alcohol 0.9%; polysorbate 80 (PSB) 2.5%; glycerin 2.4%; povidone 0.2%; or water (control), twice within 24 hours or 4 times within 48 hours, for 2 hours each time. Cells were placed back in growth media after the treatments. Cells were observed with phase-contrast microscopy until the cytotoxicity assay was performed. Mouse fibroblasts had lower survival in only the PSB-treated cells compared to the control ( < .0001) after 24 hours. After 48 hours, PSB killed nearly all mouse fibroblasts ( < .0001). BKC decreased fibroblast survival in a dose-dependent manner ( < .001). In human TM fibroblasts, all excipients except povidone and benzyl alcohol after 24 hours and povidone after 48 hours reduced cell survival compared to control ( = .012 to < .0001). The cytotoxicity of BKC in human TM fibroblasts was also dose dependent (<.0001). PSB was less cytotoxic to human fibroblasts. Phase-contrast images mirrored the cytotoxicity findings. Polysorbate 80 and benzalkonium chloride, at concentrations found in commercial ear drops, may be cytotoxic to human and mouse TM fibroblasts. "Inactive" ingredients may need to be considered when evaluating clinical outcomes with commercial ear drops.